Substitue the expression 5-3x into the second equation
1 answer:
Answer:
<h2><u>
X= 1</u></h2>
Step-by-step explanation:
<em>y = 5 - 3x</em>
<em>5x - 4y = -3</em>
you substitute for y since you know what y equals.
so, it will then be
5x -4(5 -3x) = -3
you then multiply -4 by everything in the parenthesis
so then it will be
5x - 20 + 12x = -3
Then combine like terms
5x + 12x = 17x
then the new equation is
17x -20 = -3
the next step is to and 20 to both sides since it is negative you do the opposite.
17x - 20 = -3
<u> + 20 +20</u>
17x = 17 divide 17 by both sides sice 17 is being multiplied by x you do the opposite and divide and you get 1.
<h2><u>
so, X = 1</u></h2>
You might be interested in
Answer:
the answer is 7(4 +6)
Step-by-step explanation:
24 + 42
7(4 + 6)
Ggggggyrftgtgggfcxfdfftytyyggyyy
Answer:(125-81.25)/125 = 0.35 = 35%
Step-by-step explanation:
Answer:
Bruh why do you have to self promote in Brainly of all places?
Step-by-step explanation: